Tribological Performance of Modified Jatropha Oil Containing Oil-Miscible Ionic Liquid for Machining Applications - Amiril Sahab, Abdul Sani; Erween, Abd Rahim; Syahrullail, Samion (Springer, 2017)
Modifying physicochemical and tribological properties of a bio-based lubricant is essential in improving its lubrication performances. This paper presents the effectiveness of a fully oil-miscible ionic liquid (IL) as lubricant additive into a bio-based lubricant. Methyltrioctylammonium bis(trifluoromethylsulfonyl)imide (AIL) was selected as IL additive to improve the tribological performance of the bio-based lubricant. The additive was mixed into the bio-based lubricant at three levels of mass concentrations (1 wt.%, 5 wt.% & 10 wt.%). Tribology tests on steel/steel contacts were conducted to evaluate the lubricant samples. Test outputs were benchmarked against the neat bio-based lubricant. Results revealed the good synergistic effect of the AIL additive blended into the bio-based lubricant. MJO+AIL10% has shown good corrosion inhibition, superior friction reduction (48%), lower worn surface area (23%), excellent surface finish (46%) and increased tapping torque efficiency (8%). MJO+AIL10% provided excellent tribological performances which correspond to the energy saving and environmental benefit for sustainable machining application.